Tunicamycin Mediated Inhibition of Wall Teichoic Acid Affects Staphylococcus aureus and Listeria monocytogenes Cell Morphology, Biofilm Formation and Virulence - Zhu, Xingyue; Liu, Dongqi; Singh, Atul K.; Drolia, Rishi; Bai, Xingjian; Tenguria, Shivendra; Bhunia, Arun K. (Frontiers in Microbiology, 2018)
The emergence of bacterial resistance to therapeutic antibiotics limits options for treatment of common microbial diseases. Subinhibitory antibiotics dosing, often aid in the emergence of resistance, but its impact on pathogen’s physiology and pathogenesis is not well understood. Here we investigated the effect of tunicamycin, a cell wall teichoic acid (WTA) biosynthesis inhibiting antibiotic at the subinhibitory dosage on Staphylococcus aureus and Listeria monocytogenes physiology, antibiotic cross-resistance, biofilm-formation, and virulence. Minimum inhibitory concentration (MIC) of tunicamycin to S. aureus and L. monocytogenes was 20 - 40 µg/ml and 2.5 - 5 µg/ml, respectively, and the subinhibitory concentration was 2.5 - 5 µg/ml and 0.31 - 0.62 µg/ml, respectively. Tunicamycin pre-exposure reduced cellular WTA levels by 18-20% and affected bacterial cell wall ultrastructure, cell membrane permeability, morphology, laser-induced colony scatter signature, and bacterial ability to form biofilms. It also induced a moderate level of cross-resistance to tetracycline, ampicillin, erythromycin, and meropenem for S. aureus, and ampicillin, erythromycin, vancomycin, and meropenem for L. monocytogenes. Pre-treatment of bacterial cells with subinhibitory concentrations of tunicamycin also significantly reduced bacterial adhesion to and invasion into an enterocyte-like Caco-2 cell line, which is supported by reduced expression of key virulence factors, Internalin B (InlB) and Listeria adhesion protein (LAP) in L. monocytogenes, and a S. aureus surface protein A (SasA) in S. aureus. Tunicamycin-treated bacteria or the bacterial WTA preparation suppressed NF-κB and inflammatory cytokine production (TNFα, and IL-6) from murine macrophage cell line (RAW 264.7) indicating the reduced WTA level possibly attenuates an inflammatory response. These results suggest that at the subinhibitory dosage, tunicamycin-mediated inhibition of WTA biosynthesis interferes with cell wall structure, pathogens infectivity and inflammatory response, and ability to form biofilms but promotes the development of antibiotic cross-resistance.